Development and Validation of First-Order Derivative Spectrophotometry for Simultaneous Determination of Levocetirizine Dihydrochloride and Phenylephrine Hydrochloride in Pharmaceutical Dosage Form. (18th July 2013) - Parmar, Kaminee; Baldania, Sunil; Shah, Dimal; Chhalotiya, Usmangani; Parmar, Naimin
Abstract : A simple, precise, accurate, and economical spectrophotometric method has been developed for simultaneous estimation of levocetirizine dihydrochloride (LCT) and phenylephrine hydrochloride (PHE) by employing first-order derivative spectrophotometric method. The first-order derivative absorption at 240 nm (zero crossing point of PHE) was used for quantification of LCT and 283.2 nm (zero crossing point of LCT) for quantification of PHE. The linearity was established over the concentration range of 4–24  μ g/mL and 8–48  μ g/mL for LCT and PHE with correlation coefficients (r 2 ) 0.9964 and 0.9972, respectively. The mean % recoveries were found to be in the range of 99.14%–100.43% for LCT and 98.73%–100.83% for PHE. The proposed method has been validated as per ICH guideline and successfully applied for the simultaneous estimation of LCT and PHE in combined tablet dosage form.